Landschaftserhaltung und Möglichkeiten zur Intensivierung der Landnutzung durch Leucaena Leuoccephala im Kabupaten Sikka, Flores - Metzner, Joachim (ERDKUNDE, 1976)
The Leguminosae Leucaena leucocephala (Indonesian: Lamtoro) has been rediscovered for purposes of land conservation in Indonesia’s driest province, Nusa Tenggara Timur. In Sikka on the isle of Flores Lamtoro has brought about a complete change in the agricultural landscape. Hedges of Lamtoro are planted along contour lines, which serve to halt erosion on the tuff soils of the volcanoes and which leads to the development of terraces behind them (so called indirect terracing). The outstanding characteristics of Lamtoro are its deep root system, which is likely to improve soil structure, and its ability to fix nitrogen in the soil, thereby improving soil fertility. Thus it may form a basis for agricultural intensification. Having a high protein content its leaves may be used as a valuable fodder for a cattle- and buffalo-fattening scheme. Only a small portion of Sikka’s population who live in the mountainous interior can be resettled on the few coastal plains. Direct terracing, on the other hand, is very slow and not possible on all slopes. The Lamtoro scheme has thus to be regarded as a compromise allowing the population the continued use of its fields on the hill-slopes without increasing the erosion hazard.